Review of the Neural Oscillations Underlying Meditation - Lee, Darrin J.; Kulubya, Edwin; Goldin, Philippe; Goodarzi, Amir; Girgis, Fady (Frontiers in Neuroscience, 2018)
Objective: Meditation is one type of mental training that has been shown to produce many cognitive benefits. Meditation practice is associated with improvement in concentration and reduction of stress, depression and anxiety symptoms. Furthermore, different forms of meditation training are now being used as interventions for a variety of psychological and somatic illnesses. These benefits are thought to occur as a result of neurophysiologic changes. The most commonly studied specific meditation practices are focused attention (FA), open-monitoring (OM), as well as transcendental meditation (TM) and loving-kindness (LK) meditation. In this review, we compare the neural oscillatory patterns during these forms of meditation. Method: We performed a systematic review of neural oscillations during focused attention, open-monitoring, transcendental and loving-kindness meditation practices, comparing meditators to meditation-naïve adults. Results: FA, OM, TM and LK meditation are associated with global increases in oscillatory activity in meditators compared to meditation-naïve adults, with larger changes occurring as the length of meditation training increases. While FA and OM are related to increases in anterior theta activity, only FA is associated with changes in posterior theta oscillations. Alpha activity increases in posterior brain regions during both FA and OM. In anterior regions, FA shows a bilateral increase in alpha power, while OM shows a decrease only in left-sided power. Gamma activity in these meditation practices is similar in frontal regions, but increases are variable in parietal and occipital regions. Conclusions: The current literature suggests distinct differences in neural oscillatory activity among FA, OM, TM and LK meditation practices. Further characterizing these oscillatory changes may better elucidate the cognitive and therapeutic effects of specific meditation practices, and potentially lead to the development of novel neuromodulation targets to take advantage of their benefits.